Nozzle and seat geometry for direct injection. - Sahari, Barkawi (2006)

(untitled)
The present invention provides a nozzle and needle seat geometry for the purpose of injecting gas in supersonic jets directly into an engine combustion chamber to produce better mixes with the charger in the combustion chamber of a vehicle.